Dynamic properties of steel structures under different construction stages, ambient temperature and live load - Sanrı Karapınar , Işıl; Aras, Fuat (Revista de la Construcción. Journal of Construction, 2021)
Operational modal analysis (OMA), assessing the effect of environmental conditions on the structures has been attracting widespread interest and its results have been used for the validation of numerical models. This paper aims to validate the application of OMA on steel buildings to investigate their dynamic behavior during and after their construction. In this context, the construction stages of a steel building were monitored. With the completion of the construction, the dynamic tests were applied at different times to identify the changes in the modal characteristics of the building with respect to the temperature and service loads. Finally, the analytical model of the building was performed and the building’s dynamic properties were determined numerically. As a result, the experimentally obtained dynamic properties for the completed building were compared to those derived from numerical analysis. The results underlined the importance of slab construction for the formation of building behavior in the construction stages. Besides the effects of ambient temperature and service load on the dynamic properties of steel buildings were revealed. Finally, the lack of partition walls in the numerical model has been grasped as the main reason behind the differences between the experimentally and numerically obtained dynamic properties.